Learn to Filter: A Practical Workshop on Natural Water Filtration - Jahada Haluti, Islamiyati; Regyana Julya Huzaiva; Adisti Meysila Rawung (JKA, 2025)
Water purification is a critical issue globally, particularly in regions with limited access to clean drinking water. Natural water filtration systems, using low-cost, locally available materials, offer a sustainable solution for improving water quality. This study explores the effectiveness of natural filtration methods, focusing on sand, gravel, and activated charcoal, as part of a hands-on workshop aimed at enhancing community knowledge and practical skills in water purification. The research aimed to assess the improvement in water quality, including turbidity, bacterial contamination, and pH levels, after the filtration process. A mixed-methods approach was employed, combining water quality testing before and after filtration with participant surveys to evaluate the impact of the workshop on water quality and participants' knowledge. Results indicated significant improvements in water quality, with turbidity reduced by 80% and bacterial contamination decreased by 83%. The workshop also enhanced participants' understanding of water filtration, with 90% reporting increased confidence in replicating the techniques. The study highlights the potential of community-based education programs in promoting sustainable water purification practices and empowering individuals to address local water quality challenges